O passado subtraído da desaparição forçada: Araguaia como palimpsesto - Roberto Vecchi (Estudos de Literatura Brasileira Contemporânea)
The article approaches the aporetic topic of the forced disappearance in the context of military authoritarianism in Brazil, primarily setting the problematic character of the restitution in the case of the political “desaparecidos” deriving from the impossibility of the legal category of “restitutio ad integrum”. The historical palimpsest to be thought in this perspective is the case of the Guerrilla of Araguaia that was completely erased from the maps of the Brazilian history. The case opens the discussion on the concept of restitution in the contemporary theoretical debate. It is configured similar to the act of author, inscribed in a perspective of ethical subjectivity, similarly in this sense to what happens with another key concept of contemporaneity: the witness. Literature can be assumed in this perspective as a fertile field through which rethinking restitution. The literary case considered in the article is the novel K., by Bernardo Kucinki. Explicitly assuming a fictional pact, it makes possible to subtract – from a destruction without ruins – the precarious but possible memory of the traumatic past of the forced disappearance.